Very Low Frequency Acoustic Detection of Submarines - Dixon, William C.; Rollins, C. R. (1977)
This report examines the detectability of blade rate lines for several classes of Soviet submarines. The Naval Research Laboratory has measured low frequency (VLF) transmission loss and ambient noise at sites in the Atlantic Ocean and Norwegian Sea. The results are used to calculate the array gain necessary to detect present and furture classes of Soviet submarines at these Atlantic Ocean and Norwegian Sea sites. The results are presented for submarine speeds of interest. The problem of array size needed to obtain necessary array gain and the problem of signal spatial coherence are considered.